Factors associated with the risk of progression and decompensation of heart failure in patients with an implantable cardioverter-defibrillator - N. B. Lebedeva; I. V. Talibullin; P. G. Parfenov; A. P. Egle; O. L. Barbarash (Российский кардиологический журнал)
Aim. To analyze clinical and anamnestic factors associated with the risk of acute decompensated heart failure (ADHF) in patients with an implanted cardioverter-defibrillator (ICD) with the development of a prognostic model based on the Kuzbass registry of patients with ICD.Material and methods. Prospective follow-up of 260 patients with reduced left ventricular ejection fraction (age 59 (53; 66) years, 214 (82,3%) men) from the Kuzbass registry of patients with ICD. Of them, 156 (60%) patients had ischemic cardiomyopathy, while the rest had non-ischemic cardiomyopathy. The mean follow-up period was 4,2±2,3 years after ICD implantation. The following basic information about patients were assessed: demographic data, social status, history of the underlying disease, concomitant diseases, vital signs, standard clinical and paraclinical parameters, drug therapy. During the follow-up period, all cases of ADHF and death were analyzed.Results. A total of 54 (20,8%) patients died, of which 48 (88,9%) died due to ADHF. During the follow-up period, 34 patients were hospitalized for ADHF, of which 13 (38,2%) died. Thirty-five (13,5%) patients died in the prehospital stage due to ADHF that developed against the background of the underlying disease (10 (27%) had dilated cardiomyopathy, 1 (2,8%) — rheumatic mitral valve disease, 24 (68,6%) — ischemic cardiomyopathy). Thus, a total of 69 cases of ADHF were registered, which accounted for 26,5% of the total group. Mortality in general group from ADHF was 18,5%. According to the Kaplan-Meier curve, most deaths occurred during the first 1,5 years of follow-up.The regression model for predicting the ADHF risk included left atrium size (p=0,05), male sex (p=0,001), NYHA class (p=0,0001), left ventricular ejection fraction <40% (p=0,0001), no intake of renin-angiotensin-aldosterone system inhibitors (p=0,007) and amiodarone (p=0,028). The area under the ROC curve (AUC), sensitivity and specificity of the created model was 0,8, 69,2% and 80%, respectively.Conclusion. A set of routine clinical and anamnestic factors has been identified that makes it possible to predict the risk of ADHF in patients with ICDs, which must be taken into account before making a decision to implant the device. Particular attention should be paid to mandatory therapy for heart failure, as the main modifiable risk factor for ADHF.